Design and fabrication of portable kitchen for outdoor use - Muhammad Hafiz, Abdul Latip (2008)
The study of manufacturing was very important in order to carry out this project to ensure that the student understand on what are needs to do. This project is about designing and fabricating the Portable Kitchen to solve problems that most user encounter when doing outdoor cooking activities. First is portability and second is multipurpose. This project involves designing the kitchen by searching in the internet and on local hardware shop but unfortunately no design is appropriate. So, this product design is an original idea. After completing design process, it is made real product by many manufacturing method. This project also require to ensure the safety for the indeed of publishing. Methods and process involve in this project for instance joining using MIG welding, cutting using shearing method and a finishing processes. This project in mainly about generating a new concept of portable kitchen for outdoor use that can fulfil the need of outdoor cooking. After all process had been done, this kitchen may help us to understand the fabrication and designing process that involved in this project.